2017
DOI: 10.2196/jmir.6706
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Misconduct and Social Media: Role of Twitter in the Stimulus Triggered Acquisition of Pluripotency Cells Scandal

Abstract: BackgroundThe academic scandal on a study on stimulus‑triggered acquisition of pluripotency (STAP) cells in Japan in 2014 involved suspicions of scientific misconduct by the lead author of the study after the paper had been reviewed on a peer‑review website. This study investigated the discussions on STAP cells on Twitter and content of newspaper articles in an attempt to assess the role of social compared with traditional media in scientific peer review.ObjectiveThis study examined Twitter utilization in scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Additionally, the studies were extensively discussed in Twitter and blogs. A study of the Twitter activity related to STAP cells showed that discussions of possible misconduct took place on Twitter before the discussions in the mainstream media (Sugawara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the studies were extensively discussed in Twitter and blogs. A study of the Twitter activity related to STAP cells showed that discussions of possible misconduct took place on Twitter before the discussions in the mainstream media (Sugawara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The coverage received by the STAP cell case can be attributed to many factors, but the instrumentality of social media cannot be ignored. Although this manuscript was undergoing review, a related study was published that provided rudimentary analysis of the print and social media coverage of the STAP cell case in Japan [ 87 ]. This study confirmed that print coverage tended to lag behind social media coverage—a finding which supports other reports suggesting that news initiated and driven by public interest may indeed influence public opinion [ 9 , 88 ], or at least mainstream reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Rumors about data errors, methodological mistakes, and scientific misconduct can spread very quickly on social media such as Twitter (a popular micro-blogging platform, see https://www.twitter.com ) (da Silva Jaime & Dobránszki, 2019 ). Sugawara et al, ( 2017 ) found that discussions on scientific misconduct regarding a study on stimulus-triggered acquisition of pluripotency (STAP) cells in Japan in 2014 occurred on Twitter before they surfaced in newspapers. Retracted publications obtain fewer citations either before or after retraction than non-retracted publications (Sotudeh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…com) (da Silva Jaime & Dobránszki, 2019). Sugawara et al, (2017) found that discussions on scientific misconduct regarding a study on stimulustriggered acquisition of pluripotency (STAP) cells in Japan in 2014 occurred on Twitter before they surfaced in newspapers. Retracted publications obtain fewer citations either before or after retraction than non-retracted publications (Sotudeh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%